Dancing in/out/around/about the closet: narrating autoethnographic agency from [a] marginalized voice - Hummel, Gregory Sean, author; Griffin, Cindy L., advisor; Aoki, Eric, committee member; Brantmeier, Edward J., committee member (Colorado State University. Libraries, 2010)
The purposes of this study were threefold: (1) to understand the significance of autoethnography with the communication studies field; (2) to question the relationship between/within theoretical frameworks on identity, voice, and agency; and (3) to theorize on the affects of coming out through the lenses of identity, voice, and agency from an autoethnographic perspective. In short, the study finds autoethnographic perspectives to be a fruitful endeavor for communication scholars seeking to understand a more holistic picture of the human condition, while calling for more research to enhance theoretical conceptualizations of identity, voice, and agency. Furthermore, this study suggests that autoethnographic perspectives can offer voice to otherwise silenced identities, while also providing re/presentations for individuals who lack representation in and/or outside of the academy. Finally, this study urges individuals who avow to being an ally for marginalized individuals/groups to actively voice their support in order to create more comfortable/safe spaces within and/or outside of the classroom.
Department Head: Sue Pendell.